Role of ayurveda in the management of hypothyroidism - A case report - Alka (Babbar); Shweta Raturi (Wolters Kluwer Medknow Publications, 2022)
Compromised daily habits such as more sugar intake, lack of exercise, stress, familial tendencies, etc., lead to various lifestyle diseases impacting the normal functioning of the human body systems. Hypothyroidism is one such disease that is caused due to inadequate production of thyroid hormones. The thyroid gland regulates the body's metabolism and growth. In Ayurveda, this is attributed to a function of Agni. Clinical symptoms of this disease closely resemble Agnimandya and symptoms precipitated consequentially. A 24-year-old female patient visited the hospital with complaints of irregular menstruation, heaviness all over the body, gradual weight gain, and constipation. After thorough examination and investigations, she was diagnosed with a case of hypothyroidism with increased thyroid-stimulating hormone levels. Her ultrasound findings also showed a polycystic ovary syndrome-like presentation with mildly enlarged bilateral ovaries with multiple small follicles and increased ovarian stroma. She was effectively treated with an Ayurvedic treatment approach for 5 months (five cycles).